Augmented reality glasses as a new tele-rehabilitation tool for home use: patients' perception and expectations. (19th May 2022) - Cerdán de las Heras, J.; Tulppo, M.; Kiviniemi, A.M.; Hilberg, O.; Løkke, A.; Ekholm, S.; Catalán-Matamoros, D.; Bendstrup, E.
Abstract: Purpose of the study: Explore perceptions, expectations and challenges following a telerehabilitation programme using augmented reality glasses (ARG) in patients with idiopathic pulmonary fibrosis (IPF), chronic obstructive pulmonary disease (COPD) or recently diagnosed myocardial infarction (MI). Materials and Methods: A qualitative approach was employed to track perspectives from a range of patients with chronic lung and/or heart diseases. COPD, IPF and MI outpatients from Denmark and Finland were invited to participate. Data were collected through focus group and semi-structured in-depth interviews. Qualitative analysis was performed using standard thematic analytical approaches. A topic guide was used to explore experiences and perceptions of the ARG telerehabilitation device among participants. Results: Thirteen patients (4 MI, 2 IPF and 7 COPD), 3 women and 10 men aged 56 to 75 years (mean age 63.3 years) were allocated into one focus group (9 patients) and 4 interviews (4 patients). Twelve patients reported the added value of ARG and suggested constructive changes such as the adjustable screen/brightness, robust head fixation for exercise performance, easy to navigate interface and supported feedback based on exercise performance. Conclusion: Patients with chronic heart or lung diseases described the added value in an ARG telerehabilitation programme. Improvements for a future version of the ARG were suggested. IMPLICATIONS FOR REHABILITATION: Patients with chronic pulmonary and heart diseases have difficulties to change behaviour to a more active and healthy lifestyle, offers from the health sector to participate in rehabilitation programmes at the hospital are feasible and improves quality of life and exercise capacity. Not all the patients are capable of participating in such rehabilitation programmes due to frailty and long distance to the hospital. Telerehabilitation seems to be a potential treatment to cope with the needs expressed above. Patient involvement in the development of a telerehabilitation solution to empower chronic pulmonary and heart patients to train, ensures a positive contribution to the design of the expected augmented reality software and hardware envisioned solution for telerehabilitation. The development of a user-centered telerehabilitation platform responding to the preferences of patients with chronic disease will remove barriers that limit use and compliance and improve empowerment in future research projects.